Amidst refugee flows, irregular migration, and authoritarianism: The politics of citizenship in Turkey - Mesut Yeğen (Stiftung Wissenschaft und Politik (SWP), 2022)
With the background of the Syrian crisis, irregular migration, and authoritarianism - strengthened by the collapse of the Peace Process of the Turkish state with the Workers' Party of Kurdistan (PKK) in 2015 and the 2016 coup attempt - the Turkish government has amended the Citizenship Law, changed policies concerning refugees and irregular migrants, and re-designed access to basic citizenship rights in the last decade. Due to these amendments and changes, tens of thousands of Syrians have been awarded Turkish citizenship. A few millions of them are now settled in Turkey and exercising social and education rights without being Turkish citizens. This state of affairs contradicts previous Turkish policies for citizenship and supports the claims that the government under the Justice and Development Party (AKP) has been constructing a more Islamic and less secular Turkish nationhood. Concomitantly, the basic citizenship rights of Kurds and members of the Gulen community have been massively violated. This indicates that being Muslim or Turkish does not protect citizens from discrimination.
Keywords: 320; Turkey; Citizenship Law; Peoples' Democratic Party (HDP); Workers' Party of Kurdistan (PKK); Justice and Development Party (AKP); Gulen community; Kurds; Turkification; Syrians; Afghans; refugees; migrants